Okvirni pregled poteka, vzrokov in pomena izseljevanja Slovencev na Hrvaško - Kržišnik-Bukić, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1994)
The main characteristics of the Slovene emigration to Croatia are presented. The number of Slovenes had been increasing since the middle of the 19th century, but by the end of the 20th century it decreased considerably owing to natural assimilation in the Croatian ethnic environment and the repatriation to Slovenia. All the while, Slovene men and women in Croatia belong to urban population, maintaining friendly contacts with the majority population but also preserving their Slovene identity. As good and reliable workers in various professions as well as successful artists they were - and are suitably esteemed in the neighbouring country.
Keywords: Hrvatska; Slovenci; slovenski izseljenci